Dolphins at daybreak - Osborne, Mary Pope.; Boyce, Natalie Pope.; Murdocca, Sal; Osborne, Mary Pope. (New York : Scholastic, 1997)
It's sink or swim for Jack and Annie when the Magic Tree House whisks them off to the middle of the ocean. Luckily, they find a mini-submarine on a coral reef. Unluckily, they are about to meet a giant octopus and one very hungry shark. Will the dolphins save the day? Or are Jack and Annie doomed to be dinner?
K
This Lexile score is misreported on the back book cover by the publisher. The publisher printed 350 not 540. The publisher was in error.
b
K
Keywords: Dolphins -- Juvenile literature; Sharks -- Juvenile literature